Meningkatkan Keterlibatan dan Aksesibilitas: Strategi Promosi di Perpustakaan Universitas Megarezky Makassar - Ramadayanti, Ramadayanti; Arifin, Nur (Inkunabula: Journal of Library Science and Islamic Information, 2024)
This study examines promotional strategies aimed at enhancing engagement and accessibility at the University of Megarezky Makassar Library. Against the backdrop of challenges in increasing participation and utilization of library services, this research identifies various effective approaches to expand reach and improve user engagement. The methods employed include leveraging digital technologies, such as social media and library applications, as well as organizing promotional activities involving the academic community. The results of these strategies demonstrate that an integrated and responsive approach not only increases user awareness of library services but also facilitates access to information resources. These findings provide valuable insights for developing more effective promotional strategies, with the aim of optimizing engagement and accessibility for all users within the university environment. Abstrak Penelitian ini membahas strategi promosi untuk meningkatkan keterlibatan dan aksesibilitas di Perpustakaan Universitas Megarezky Makassar. Dengan latar belakang tantangan dalam meningkatkan partisipasi dan pemanfaatan layanan perpustakaan, penelitian ini mengidentifikasi berbagai pendekatan efektif untuk memperluas jangkauan dan meningkatkan keterlibatan pengguna. Metode yang diterapkan meliputi pemanfaatan teknologi digital, seperti media sosial dan aplikasi perpustakaan, serta penyelenggaraan kegiatan promosi yang melibatkan komunitas akademik. Hasil dari strategi ini menunjukkan bahwa pendekatan yang terintegrasi dan responsif tidak hanya meningkatkan kesadaran pengguna tentang layanan perpustakaan tetapi juga mempermudah akses ke sumber daya informasi. Temuan ini memberikan wawasan berharga untuk pengembangan strategi promosi yang lebih efektif, dengan harapan dapat mengoptimalkan keterlibatan dan aksesibilitas bagi seluruh pengguna di lingkungan universitas.